The Representation of Ecological Subjectivity in the Poetry of Qāsim Ḥaddād: An Ecocritical Perspective by Lawrence Buell - Muhammad azwar; Tafkur Bahril Wahid; Silmi Malina Binta; Anisa Dwi Nurchayati (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2026)
This study examines ecological subjectivity in Qāsim Ḥaddād’s poems through Lawrence Buell’s ecocritical framework. This study is driven by the escalating global ecological crisis rooted in anthropocentrism, a paradigm that positions nature merely as an object of human exploitation. This research aims to reveal how Ḥaddād reconstructs the relationship between humans and nature through the affirmation of nature’s subjectivity, while simultaneously deconstructing the anthropocentric worldview. Employing a descriptive-qualitative method with an ecocritical approach, the study analyzes representations of nature in four poems through four major categories of ecological subjectivity: agency, communication, volition, and ecological morality. The findings demonstrate that Ḥaddād represents nature not as a passive background, but as an active subject capable of acting, communicating, expressing volition, and embodying ethical values. Trees, forests, soil, and other natural entities are portrayed through symbolic and semiotic forms of communication that challenge the hierarchical separation between humans and nature. This study contributes to the development of Buell’s ecocriticism in the context of contemporary Arabic poetry and expands discussions on ecological subjectivity and anti-anthropocentric discourse in Arabic literary studies.